The Posterior Parietal Cortex in Adaptive Visual Processing. Issue 11 (November 2018) - Xu, Yaoda
Abstract : Although the primate posterior parietal cortex (PPC) has been largely associated with space, attention, and action-related processing, a growing number of studies have reported the direct representation of a diverse array of action-independent nonspatial visual information in the PPC during both perception and visual working memory. By describing the distinctions and the close interactions of visual representation with space, attention, and action-related processing in the PPC, here I propose that we may understand these diverse PPC functions together through the unique contribution of the PPC to adaptive visual processing and form a more integrated and structured view of the role of the PPC in vision, cognition, and action. Highlights: The primate PPC was traditionally viewed as being involved in spatial, attention, and action-related processing. However, a growing number of studies have reported the direct representation of diverse action-independent nonspatial visual information in the PPC during both perception and visual working memory. Functional and anatomical evidence shows that direct representation by the PPC of action-independent nonspatial visual information is distinct and at the same time closely interacts with the role of the PPC in space, attention, and action-related processing. Given the involvement of the PPC in multiple distinctive, yet interconnected mental operations, here I propose that we may understand these diverse PPC functions together through the unique contribution of the PPC to adaptive visual processing. Understanding the functions of PPC through its contribution to adaptive visual processing both accommodates each distinctive PPC function and allows us to form a more integrated and structured view regarding the overall role of the PCC in vision, cognition, and action.